What Are the Limitations and Challenges of Swab-Based DNA Sampling? - Brigitte Bruijns (Forensic Sciences, 2024)
Selecting the optimal sampling method is an essential component of the DNA analysis process. Errors or omissions in targeting and gathering relevant samples can significantly reduce the likelihood of obtaining a valuable DNA profile, affecting the profile’s quality and evidential value and ultimately hindering its ability to support the justice system. While DNA typing techniques have become significantly more sensitive in recent years, there is an ongoing need for further advancements in the recovery of DNA from crime scenes. It is essential to improve the accuracy and reliability of forensic investigations, particularly in cases where only tiny amounts of DNA are present, such as touch DNA samples or degraded forensic evidence. Parameters, including swab material, type of substrate, and swabbing protocol, that influence the efficiency of a swab are discussed in this review. This is followed by a literature review of studies that have compared swab types and/or other sampling conditions. While swabs are the most-used collection tools at a crime scene, alternatives are available. These alternatives are reviewed, including their advantages and disadvantages. A critical discussion and conclusions make clear that, unfortunately, neither swabs nor their alternatives are highly effective in recovering DNA from a substrate.